"Save Ralph" Sebagai Media Kampanye Uji Coba Kosmetik Tanpa Hewan (Analisis Semiotika Charles S. Peirce) - Natalia, Della; Joni, I Dewa Ayu Sugiarica; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium, 2023)
Mockumentary short animation film ‘Save Ralph’ is a campaign made by animal protection organizations and charity fundraiser, Humane Society International. This campaign film raised the issue of cosmetic animal testing represented as signs in every scene that contains messages. This study aims to analyze the messages from ‘Save Ralph’ as a cruelty-free campaign media. This study uses Charles Sanders Peirce’s analytical semiotic theory by examining the signs as representamen, object, and interpretant. This research uses qualitative descriptive methods, using a constructive paradigm. Primary data were obtained from this study's object, based on its scenes. The result of this study shows the meaning contained in ‘Save Ralph’ is to encourage the cosmetic animal testing free represented by the negative impacts experienced by animals as the victim of cosmetic testing.